Laparoscopic-assisted anorectal pull-through vs. posterior sagittal anorectoplasty for treating high anorectal malformations: a single-center experience - Mohammad Anas AlShawa; Ahmed Al Wusaibie; Saud Al Shanafey (SpringerOpen, 2022)
Abstract Background/purpose Surgical management of high-type anorectal malformations (ARM) has evolved over the years with the widespread of the laparoscopic approach over the last two decades. This study aims to compare the outcome of patients with high anorectal malformation (ARM) managed with laparoscopic-assisted anorectal pull-through (LAARP) vs. the open posterior sagittal anorectoplasty (PSARP) at a single Institution. Methods A retrospective chart review of pediatric patients, who were managed for high-type ARM at our institution, was performed for the period 2000-2015. Nine were excluded because of a lack of important data. Demographic data, surgical approach, associated anomalies, and complications were collected. Functional outcome was measured using the modified clinical scoring for the defecation function of the Japanese study group of anorectal anomalies. Comparison between groups was done using the T test for continuous variables and the Fisher-exact test for proportions. P < 0.05 is considered statistically significant. Results There were 82 patients with high type imperforate anus (59 males and 23 females) 73% had laparoscopy vs. 27% open. Type of fistulae were rectourethral (36), rectovesical (12), no fistula (19), and (15) cloaca anomalies. Patients underwent surgery at a mean age 8.4 (laparoscopy) vs. 10.1 (open) months (P value = 0.14). There was no difference between the two groups regarding weight at the surgery or associated anomalies, except for VACTRAL and genitourinary malformations which were more among the laparoscopic group (8 vs. 1). There was no statistical significance for all elements of defecation function score: sensation, constipation, and soiling (P values 0.17, 0.6, 0.07, respectively). There was no difference between the two groups regarding rectal prolapse (P = 0.06), whereas rectal stenosis is more in PSARP compared to LAARP (P = 0.03). The hospital stay was significantly shorter in LAARP 7.1 vs. 9.4 (P = 0.006). Conclusions The defecation function and complication rate for both laparoscopic and open groups were almost similar. This may justify the preference of the laparoscopic approach over the open one, given its minimally invasive nature.